2022
DOI: 10.1155/2022/2372257
|View full text |Cite
|
Sign up to set email alerts
|

ERCP-Related Adverse Events in Primary Sclerosing Cholangitis: A Systematic Review and Meta-Analysis

Abstract: Background and Aims. While endoscopic retrograde cholangiopancreatography (ERCP) is a valuable diagnostic and therapeutic tool in primary sclerosing cholangitis (PSC), there is conflicting data on associated adverse events. The aims of this systematic review and meta-analysis are to (1) compare ERCP-related adverse events in patients with and without PSC and (2) determine risk factors for ERCP-related adverse events in PSC. Methods. Embase, PubMed, and CENTRAL were searched between January 1, 2000, and May 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Few studies have compared the rates of ERCP adverse events in those with and without PSC [ 21 ]. A systematic review and meta-analysis [ 22 ] found a significant increase in cholangitis after ERCP in PSC group, compared to patients without PSC (OR 3.263, 95% CI 1.076–9.896; p = 0.037). This increase in infection was observed despite the consistent antibiotic use in most studies, in agreement with previous research, that reported difficulties in the clearance of bacterial overgrowth in PSC patients [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have compared the rates of ERCP adverse events in those with and without PSC [ 21 ]. A systematic review and meta-analysis [ 22 ] found a significant increase in cholangitis after ERCP in PSC group, compared to patients without PSC (OR 3.263, 95% CI 1.076–9.896; p = 0.037). This increase in infection was observed despite the consistent antibiotic use in most studies, in agreement with previous research, that reported difficulties in the clearance of bacterial overgrowth in PSC patients [ 23 ].…”
Section: Resultsmentioning
confidence: 99%